Phenolic content and antioxidant capacity of Lagerstroemia speciosa (Banaba) and Blumea balsamifera (Sambong) herbal teas sold on-line in the Philippines: A cost-effectiveness analysis - Deocaris, Custer C; L Micor, Jose Rene; Zhang, Muxi; Alinsug, Malona V; E Mojica, Elmer Rico (Bangladesh Journal of Scientific and Industrial Research, 2023)
Herbal teas are widely consumed for their health benefits. In this study, the phenolic content and antioxidant capacity of six commercially available banaba (Lagerstroemia speciosa) and sambong (Blumea balsamifera) herbal teas were analyzed. The antioxidant activity was measured using DPPH and ABTS assays, with L. speciosa teas exhibiting higher activity than B. balsamifera teas. The phenolic content was determined using the Folin-Ciocalteu method and showed a direct correlation with antioxidant activity. The market prices based on unit phenolic content and antioxidant activity varied widely with different brands sold online indicating the need for better quality control of the teas analyzed. Bangladesh J. Sci. Ind. Res. 58(4), 265-270, 2023